Validation of a single question for the assessment of past three-month alcohol consumption among adolescents. (1st November 2021) - Levy, Sharon; Wisk, Lauren E.; Chadi, Nicholas; Lunstead, Julie; Shrier, Lydia A.; Weitzman, Elissa R.
Highlights: Explores a single question regarding past 3-month alcohol consumption among youth. Highly correlated with the criterion standard measure of alcohol consumption. The question is brief enough to embed in the electronic medical record. The measure can be used in trials enrolling large numbers of primary care patients. Abstract: Background: Screening, Brief Intervention, and Referral to Treatment (SBIRT) for substance use is increasingly used in clinical care. Despite its endorsement by several professional societies, the U.S. Preventive Services Task Force has found the evidence base for adolescent SBIRT to be insufficient. A measure of substance use that is brief enough to embed in the electronic medical record could be used in pragmatic trials that enroll large numbers of primary care patients, facilitating research in this area. Methods: Participants aged 14–18 years (N = 492) completed an electronic survey that included a 90-day Timeline Follow Back (TLFB) Calendar, considered the criterion standard, along with three survey questions about the frequency of their alcohol use: days of use in the past three months, average days of use per week in the past three months, and average days of use per month in the past year. We calculated the correlation between the number of days reported on each of the three questions and the total number of days of use reported on the TLFB. Results: The question on number of days of use in the past three months was highly correlated with alcohol consumption frequency on the 90-day TLFB assessment (rho = 0.903). Other items displayed lower but satisfactory correlation with the TLFB (rho = 0.719−0.830). Conclusions: A single question about past 3-month frequency of alcohol use was highly correlated with alcohol use frequency on the criterion standard TLFB among adolescents presenting for routine primary care.